Influence of heavy metals on cancer accommodation: A literature review (Research, Society and Development, 2021)
Objective: To report the influence of heavy metals in the onset of cancer, thus describing the main metals that hold this possibility, also citing the types of cancers commonly caused by exposure to these metals. Methodology: This is a literature review of a descriptive and qualitative nature about the influence of heavy metals on cancer. The study was carried out from December 2020 to February 2021, by analyzing the databases: Pubmed, SciELO and Lilacs. The search and selection of materials were carried out based on previously established inclusion and exclusion criteria, which totaled 48 materials, these published between the years 2000 to 2021, thus composing the present study. Results and discussion: Even in low concentrations, exacerbated exposure to heavy metals promotes chronic inflammation, which triggers oxidative stress, and subsequently the process of carcinogenesis. Among the main metals involved in the carcinogenesis process, we can mention: copper, mercury, cobalt, nickel, cadmium, chromium, arsenic, silver and lead. Regarding the types of cancers affected by continued exposure to these metals, there are: lung, skin, ovary, breast, stomach, prostate, brain and larynx cancers. Conclusion: Heavy metals have a great influence on the process of carcinogenesis, which is intrinsically linked to sequenced exposure and bioaccumulation of these elements. Numerous are heavy metals with the potential to trigger the development of cancers, which reflects in the variability of tissues and organs affected and the diversity of tumors in humans.